Artificial Intelligence in ELT: Advancing Adaptive and Personalized Language Learning - Budiyanto, Darmawan; Tridinanti, Gaya; Saputri, Kurnia; Apriani, Eka; Sartika, Dewi (Universitas Pendidikan Mandalika, 2025)
This study investigates the pedagogical benefits and challenges of integrating Artificial Intelligence (AI) technologies in English Language Teaching (ELT) classrooms. With the rapid advancement of AI, its application in education, particularly in language learning, has generated increasing scholarly and practical interest. A mixed-methods approach was adopted, combining quantitative data from a survey of 120 English teachers in Palembang with qualitative insights from in-depth interviews with 10 teachers. The survey employed a Likert-scale questionnaire to assess the perceived impact of AI, while thematic analysis was applied to the interview data. The findings indicate that 78% of respondents agreed AI supports personalized learning, 82% believed it enhances student engagement, and 75% reported increased student motivation. Nevertheless, 45% of teachers identified technical barriers such as unreliable internet access, and 52% expressed concerns over insufficient teacher training. Qualitative evidence reinforced these perspectives, with teachers highlighting the irreplaceable role of human interaction and warning against excessive reliance on AI tools. Overall, the study suggests that AI can enrich ELT by providing tailored content and real-time feedback, but its effective integration depends on addressing infrastructural limitations and strengthening teacher preparedness. Teachers also emphasized balancing AI with traditional pedagogies to preserve the essential human dimension of language learning. Beyond the classroom, these findings carry broader implications for policy and practice. They highlight the need for systemic reforms in infrastructure, sustained professional development, and stronger alignment between AI tools and curriculum goals. If strategically implemented, AI has the potential not only to enhance ELT practices but also to advance equitable, future-ready education systems.